Access to Trade Finance in Times of Crisis - Wang, Jian-Ye (International Monetary Fund, 2006)
Trade finance has long been an important component of international financial flows. Firms in emerging market economies, in particular, rely heavily on bank-financed trade credits to support their export and import activities. This book examines why and how much trade finance flows decline during financial crises, with case studies of several Asian and Latin American countries. The authors draw from the analysis to present options for mitigating trade finance declines in the event of future crises.